Partnerships for development. Assessing the impact potential of cross-sector partnerships. (July 2021) - Vestergaard, Anne; Langevang, Thilde; Morsing, Mette; Murphy, Luisa
Highlights: Analysis of potential of Business-NGO partnership to alleviate poverty in Ghana. Partnerships for development risk merely serving the interests of the business. Partnership assessment frameworks must focus on impact potential for the poor. Assessment framework for impact potential of partnerships for development is proposed. Abstract: Over the past two decades, research as well as practice have praised the promise of cross-sector partnerships as the new transnational governance mechanism for reaching international development goals. Although there is general consensus that partnerships have the potential to contribute to development in the Global South, there is, however, increasing suspicion that in practice, they often do not. On the basis of an empirical analysis of a North-South Business-NGO partnership for poverty alleviation in Ghana, we show that existing assessment frameworks in the management literature are useful but insufficient for assessing partnerships in a development context. Through an integration of theoretical and empirical insights, we propose a novel framework, Partnerships for Development, which puts forward organizational preconditions for cross-sector partnerships to produce societal impact in the Global South, giving way to an assessment system for cross-sector partnerships in terms of their impact potential.